Enhanced electromagnetic interference shielding of carbon fiber/cement composites by adding ferroferric oxide nanoparticles. (1st October 2017) - Liu, Zhifang; Ge, Heyi; Wu, Jiaming; Chen, Juan
Highlights: The introduction of nano-Fe3 O4 into CF/cement composites could significantly enhance the EMI SE. The incorporation of 5 wt% nano-Fe3 O4 along with 0.4 wt.-% CF in the cement led to a SE of 29.8 dB. The excellent EMI SE could be attributed to the synergistic effect of CF and nano-Fe3 O4 . Abstract: Ferroferric oxide (Fe3 O4 ) nanoparticles were introduced into carbon fiber (CF)/cement composites to enhance the electromagnetic interference (EMI) shielding effectiveness (SE) in X-band (8.2–12.4 GHz). The spherical Fe3 O4 nanoparticles were synthesized through solvothermal method, whose average diameter was about 30–50 nm. It was observed that incorporation of Fe3 O4 nanoparticles (5 wt%) along with 0.4 wt% CF in the cement matrix led to a shielding effectiveness of 29.8 dB, which had 34.4% increase than that of CF/cement composite. The excellent EMI shielding property was attributed to the synergistic effect between CF and Fe3 O4 nanoparticles. SEM revealed the homogeneous dispersion of Fe3 O4 and CF in the cement matrix. The CF/Fe3 O4 /cement composite is believed to be a promising material for high EMI shielding.